2016
DOI: 10.21273/hortsci.51.4.403
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Seed and Clonal Propagation of the Mediterranean Aromatic and Medicinal Plant Teucrium capitatum

Abstract: The effect of various pretreatments, culture conditions, and storage time on in vitro germination of seeds, as well as the effect of explant origin and plant growth regulators on in vitro propagation of Teucrium capitatum L. (Teucrium polium sp. capitatum Arcang., Lamiaceae) were examined. Seeds, collected from native plants and stored at room temperature for 3, 7, and 12 months, were cultured for germination in vitro in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 52 publications
6
21
0
Order By: Relevance
“…Microshoots rooted at equally high percentages at IBA concentrations from 0.0 to 4.0 mg • L -1 , in agreement with reports of L. thiniense (Lled o et al, 1996) and L. cavanillesii (Amo-Marco and Ibañez, 1998) but in contrast to our initial results that showed higher rooting percentages in rooting media supplemented with IBA compared with the hormone-free medium (Martini and Papafotiou, 2016). However, this discordance in our results could be attributed to the improvement of rooting capacity of microshoots as subcultures progressed, which has been reported for another Mediterranean xerophyte Teucrium capitatum L. (Papafotiou and Martini, 2016) as well as for various fruit trees (Al-Maarri et al, 1994;Hou et al, 2010;Noiton et al, 1992). The increase in the IBA concentration in the medium led to an analogous increase in callus formation at the base of microshoots, as observed in P. zeylanica (Sahoo and Debata, 1998;Selvakumar et al, 2001).…”
Section: Discussionsupporting
confidence: 44%
“…Microshoots rooted at equally high percentages at IBA concentrations from 0.0 to 4.0 mg • L -1 , in agreement with reports of L. thiniense (Lled o et al, 1996) and L. cavanillesii (Amo-Marco and Ibañez, 1998) but in contrast to our initial results that showed higher rooting percentages in rooting media supplemented with IBA compared with the hormone-free medium (Martini and Papafotiou, 2016). However, this discordance in our results could be attributed to the improvement of rooting capacity of microshoots as subcultures progressed, which has been reported for another Mediterranean xerophyte Teucrium capitatum L. (Papafotiou and Martini, 2016) as well as for various fruit trees (Al-Maarri et al, 1994;Hou et al, 2010;Noiton et al, 1992). The increase in the IBA concentration in the medium led to an analogous increase in callus formation at the base of microshoots, as observed in P. zeylanica (Sahoo and Debata, 1998;Selvakumar et al, 2001).…”
Section: Discussionsupporting
confidence: 44%
“…Microshoots rooted at 95% on half-strength Hf MS medium (Table 6, Figure 1J). Although, auxins are known to play an important role in root induction through their effect on first cell divisions that lead to root formation (Farooq et al, 2008), microshoots of a number of Mediterranean xerophytes, as A. barba-jovis, Ballota acetabulosa, C. nepeta, L. monopetalum (Papafotiou and Martini, 2016;Vlachou et al, 2016aVlachou et al, , 2017aVlachou et al, , 2017b, have been found to root on full-or half-strength MS medium without an auxin. Half-strength MS medium is quite often used successfully, as in the present study, since rather low nutrient concentrations positively affects rooting (Murashige, 1979;Saha et al, 2011;Vlachou et al, 2017aVlachou et al, , 2017bZhang et al, 2017).…”
Section: In Vitro Rooting and Ex Vitro Acclimatizationmentioning
confidence: 99%
“…The use of seedling-origin explants for in vitro cultures initiation usually results in high proliferation rate in Mediterranean species (Papafotiou et al, 2013;Papafotiou and Martini, 2016). Further, propagation by seed enhances genetic diversity that is desirable when native plants are used for natural landscape restoration, and contributes to the selection of genotypes with high pharmaceutical value (Sarasan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Micropropagation could facilitate the introduction of suitable clones to the pharmaceutical industry as well as breeding programs. The use of seedlings as stock plant material for micropropagation could lead to a high proliferation rate like in other Mediterranean native species (Papafotiou and Martini, 2016;Papafotiou et al, 2013). Further, the use of seedlings for either in vitro or ex vitro propagation could enhance the higher genetic diversity, which is desirable when native plants are reintroduced in the landscape, or contribute to the selection of particular genotypes of high medicinal value (Sarasan et al, 2011).…”
mentioning
confidence: 99%